Development as Institutional Change: The Pitfalls of Monocropping and the Potentials of Deliberation - Peter Evans (Studies in Comparative International Development, Winter 2004, Vol. 38, No. 4, pp. 30-52., 2004)
Development theory has moved from a single-minded focus on capital accumulation toward a more complex understanding of the institutions that make development possible. Yet, instead of expanding the range of institutional strategies explored, the most prominent policy consequence of this "institutional turn" has been the rise of "institutional monocropping": the imposition of blueprints based on idealized versions of Anglo-American institutions, the applicability of which is presumed to transcend national circumstances and cultures. The disappointing results of monocropping suggest taking the institutional turn in a direction that would increase, rather than diminish, local input and experimentation. The examples of Porto Alegre, Brazil, and Kerala, India, reinforce Amartya Sen's idea that "public discussion and exchange" should be at the heart of any trajectory of institutional change, and flag potential gains from strategies of "deliberative development" which rely on popular deliberation to set goals and allocate collective goods.